Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/nuf.12297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resilience on intolerance of uncertainty in nursing university students

Abstract: Purpose: Nursing students must cope in a complex and uncertain society. We identified the relationship between resilience and intolerance of uncertainty (IOU) in nursing students. Methods: Data were collected from November 10 to 20, 2016, from 134 Korean nursing students (male = 21, female = 113; first-year = 39, second-year = 39, thirdyear = 35, and fourth-year = 21), using a questionnaire. The measures in this study included resilience and IOU.Results: Differences in IOU relating to participants' general cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
1
15
0
4
Order By: Relevance
“…It is known that people experience uncertainty during the Covid-19 pandemic process, and in this case, individuals' resilience levels are expected to be low ( Robichaud, 2013 ). Similarly, Lee (2018) revealed that individuals with high levels of intolerance of uncertainty have low levels of self-regulation skills, interpersonal relationships, positive tendencies and resilience. According to the results of the current study, there is a significant negative relationship between intolerance to uncertainty and Covid-19 fear and resilience and this result concurs with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that people experience uncertainty during the Covid-19 pandemic process, and in this case, individuals' resilience levels are expected to be low ( Robichaud, 2013 ). Similarly, Lee (2018) revealed that individuals with high levels of intolerance of uncertainty have low levels of self-regulation skills, interpersonal relationships, positive tendencies and resilience. According to the results of the current study, there is a significant negative relationship between intolerance to uncertainty and Covid-19 fear and resilience and this result concurs with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the majority of the nursing students reported high state resilience related to factor 2 (items: 1-2, 4, 7-8, 14-15). Previous studies have shown that resilience among nursing students was in uenced by interpersonal skills, self-regulation skills, and positive tendencies [45,46]. It has been argued that these skills contribute to success in academic and professional life [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Uncertainty occurs when perceptions and behaviors do not respond appropriately to unexpected situations. This situation decreases the ability to do things right (Jeong-Sook, 2018). Kasperson (2008) defines uncertainty as a situation in which the direction of change is relatively well known, but the importance of events and their consequences cannot be predicted with any prediction of their probability of occurrence.…”
Section: Intolerance Of Uncertaintymentioning
confidence: 99%